Pengaruh Manajemen Pembelajaran Terhadap Kinerja Guru untuk Mewujudkan Prestasi Belajar Siswa - Ridwan Setiawan; Minda Indrianny (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
The problem that occurs in education today is that student achievement is still not optimal. The low level of learning management is thought to be the result of the lack of maximum teacher performance. This study aims to analyze learning management on teacher performance in realizing student achievement. This research method is a descriptive analysis method with survey techniques, observation and documentation studies. While the data analysis technique used to answer the research hypothesis is statistics with a path analysis model. The population and the respondents in this study are 70 teachers of SMKAl-Mukhtariyah and SMK Iqro.Based on the test, the value of Fcount is greater than Ftable, which is fcount = 2.5411> Ftable = 1.997. From this value, it can be concluded that H0 is rejected and H1 is accepted, so the learning management variable (X) affects teacher performance (Y) to realize student achievement (Z) at SMK Al-Mukhtariyah and SMK Iqro Garut.